2017
DOI: 10.4253/wjge.v9.i2.61
|View full text |Cite
|
Sign up to set email alerts
|

Gastric intestinal metaplasia is associated with gastric dysplasia but is inversely correlated with esophageal dysplasia

Abstract: AIMTo determine which clinical factors might be associated with gastric intestinal metaplasia (IM) in a North American population.METHODSPathology and endoscopy databases at an academic medical center were reviewed to identify patients with and without gastric IM on biopsies for a retrospective cohort study. Patient demographics, insurance status, and other clinical factors were reviewed.RESULTSFour hundred and sixty-eight patients with gastric IM (mean age: 61.0 years ± 14.4 years, 55.5% female) and 171 witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Most of the studies estimated the incidence of IM in patients underwent EGD and had biopsies to be less than 10% (3). In our study, the incidence of IM reported 17.3% may be due to late detection and lack of routine cancer screening programs.…”
Section: Clinical Characteristicsmentioning
confidence: 53%
See 4 more Smart Citations
“…Most of the studies estimated the incidence of IM in patients underwent EGD and had biopsies to be less than 10% (3). In our study, the incidence of IM reported 17.3% may be due to late detection and lack of routine cancer screening programs.…”
Section: Clinical Characteristicsmentioning
confidence: 53%
“…Atrophic gastritis (AG) and intestinal metaplasia (IM) are established premalignant gastric lesions (1). Incidence of gastric cancer (GC) is the 5th among cancers worldwide with more than 95% are adenocarcinomas (2) and the 3rd cause of cancer-related deaths worldwide (3). Recently, H. pylori infects more than half of the population in developing countries leading to a sequelae of chronic gastritis, AG, IM, and finally invasive gastric carcinoma in untreated patients (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations